PRIMARY MENINGOENCEPHALITIS CAUSED BY NAEGLERIA FOWLERI: A MINI REVIEW - Hassan Bin-Asif et al (Baqai Journal of Health Sciences)
The recent outbreak of primary meningoencephalitis caused by free-living amoebae (FLA), Naegleria fowleri, has gained increasing attention due to their confirmed fatality. It is caused by the entrance of contaminated water into nasal passage mainly by ablution practices. The symptoms include severe headache, nausea, vomiting along with fever finally leading to death. FLA other than N. fowleri such as Acanthamoeba and Balamuthia species are also harmful because they are vectors of many bacterial pathogens including Vibrio, Pseudomonas, Legionella, Enterobacter and Mycobacterium species which help them to feed and colonize in environments, thus contributing to their pathogenesis and transferability to their hosts. Pakistan, being an underdeveloped country, faces long-term shortfalls of electricity resulting in serious water scarcity leading to public dependence on stored water resources, which are breeding hubs for FLA. The rationale of the present review is to highlight the importance of N. fowleri and primary meningoencephalitis and to investigate the recent outbreak in Pakistan.